Evaluation of a micro-cogeneration unit with integrated electrical energy storage for residential application. (15th January 2021) - Uchman, Wojciech; Kotowicz, Janusz; Li, Kin Fun
Highlights: A micro-cogeneration model was prepared for the time-domain simulation. The model includes electrical energy storage. The model takes into account the progressive degradation of the battery. The prosumer's level of self-sufficiency has been significantly increased. Abstract: This paper focuses on the difference between the application of a micro-cogeneration (μCHP) device (the reference case), and an integrated system consisting of a micro-cogeneration unit combined with electrical energy storage. A model of the analyzed μCHP system was previously developed by the authors and validated using experimental data. The model of the system was enhanced with an electrical energy storage model that takes into account the progressive degradation of the battery. The main novelty of the research that has been presented in this paper lies in a significant contribution to the time-domain modeling of a micro-cogeneration device with integrated electrical energy storage. A small time step has been used here in order to balance the electrical section of the model. For the reference μCHP-only system, the demand self-coverage fluctuates on an annual basis within the range of 21.6–33.9%. The results indicate a favorable effect of the implementation of electricity storage with the micro-cogeneration device, from the point of view of self-consumption. The use of a 5 kWh storage capacity increased the prosumer's level of self-sufficiency to 41.2–59.9%. Results of the study are useful when the structure of distributed energy system is considered.